Development Gaps in the Sud Muntenia Region of Romania - Marioara Iordan; Lucian-Liviu Albu; Ion Ghizdeanu; Mihaela Nona Chilian; Tiberiu Diaconescu (European Regional Science Association (ERSA), 2013)
Development gaps are a common feature throughout the regions of the European Union, and Romania is no exception. Despite all the political and financial efforts, the convergence process is lengthy and complex, and the gaps with the deepest economic and social roots are the most difficult to be dealt with. Using a broad range of indicators and statistical and econometric techniques, the authors present a detailed picture of the development gaps and their dynamics in the Sud Muntenia region of Romania. The results show the presence of an overall development process in the region and its counties, accelerated after the accession of Romania to the European Union, but also hit by the global crisis. The inter-county and intra-county economic and social imbalances however persist, and the inadequate use of territorial resources is still an issue to be addressed by the regional and local government authorities and the private actors. Policy recommendations are proposed to address the challenges and threats to the balanced development of the Sud Muntenia region of Romania, especially considering the significant changes in the implementation of the regional development policy envisaged by the Romanian government in the very near future.
Keywords: O18; R11; R15; R58; 330; regional development; territorial development; development gaps; regional cohesion; regional development policy